CURRICULUM AS A MIRROR OF IDEOLOGICAL AFFILIATION: Rethinking Pesantren Typologies in the Landscape of Indonesian Islamic Organizations - Hidayati, Zuhriyyah; Maulidi, Achmad; Niam, Khoirun; Zainiyati, Husniyatus Salamah (UIN Sumatera Utara, 2025)
Abstract: The traditional classification of pesantren into salaf, khalaf, or mixed categories no longer captures the rich diversity of contemporary Islamic boarding schools in Indonesia. This study proposes a revised typological framework that considers the ideological and organizational affiliations of pesantren—such as NU) Muhammadiyah, Persis, Shia, and LDII. Employing qualitative library research, the analysis draws from institutional records, curriculum documents, and scholarly literature. Findings reveal that each affiliation manifests distinct educational visions: NU emphasizes tafaqquh fi al-din through classical texts; Muhammadiyah blends national education with reformist Islam; Persis promotes rationalism and anti-madhhab discourse; Shia pesantren foreground philosophy and logic; and LDII implements a closed, tiered system. The study argues for redefining pesantren typology through ideological and pedagogical lenses, offering a more accurate framework for scholars, educators, and policymakers engaging with Indonesia’s pluralistic Islamic education landscape.Keywords: Curriculum, Pesantren Typology, Islamic Education, Indonesian Islamic Organizations, Religious Affiliation.